Detection of Newcastle disease virus. - Yusoff, Khatijah; Kho, Chiew Ling; Mohd Lila, Mohd Azmi; Arshad, Siti Suri (2007)

(untitled)
A method for detection of Newcastle disease virus in a biological sample comprising (a) the extraction of mRNA from the sample (b) converting the mRNA from step (a) with reverse transcriptase under conditions allowing for the production of cDNA; ? amplifying the cDNA from step (b) by polymerase chain reaction to form an amplified PCR product (d) converting the amplified PCR product from step ? with a pair of nested primers to form a nested labelled PCR streptavidin-coated microtiter plate; (f) adding a peroxidase substrate to the immobilised product from step (e) to produce a coloured reaction product; and (g) detecting the resulting coloured reaction product using an ELISA reader.